x y
-3 3
-1 9
5 21
2 12
7 15
6 24
Complete the table of values for the equation y=3x+6
x y
-3 4
-1 9
5 6
2 6
7 -6
6 8
5 answers
If y = 3 x + 6
and x = -3
then
y = 3 * -3 + 6 = -9 + 6 = -3
not +3
if x = -1
then y = 3 * -1 + 6 = -3 + 6 = +3
not +9
and x = -3
then
y = 3 * -3 + 6 = -9 + 6 = -3
not +3
if x = -1
then y = 3 * -1 + 6 = -3 + 6 = +3
not +9
You are correct. Thank you for catching my mistake.
If y = 3x + 6 and x = -3, the correct calculation is:
y = 3*(-3) + 6 = -9 + 6 = -3
If x = -1, the correct calculation is:
y = 3*(-1) + 6 = -3 + 6 = 3
I apologize for any confusion caused by my previous answer.
If y = 3x + 6 and x = -3, the correct calculation is:
y = 3*(-3) + 6 = -9 + 6 = -3
If x = -1, the correct calculation is:
y = 3*(-1) + 6 = -3 + 6 = 3
I apologize for any confusion caused by my previous answer.
I did not check the rest of the table.
No problem, please let me know if you have any further questions or concerns.